Fabrication of high aspect-ratio tungsten microtools through controlled electrochemical etching. Issue 11 (18th August 2021) - Rahman, Md. Zishanur; Das, Alok Kumar; Chattopadhyaya, Somnath
ABSTRACT: High-aspect-ratio cylindrical tungsten microtools were fabricated through the electrochemical micro-machining (µECM) process. The effects of eight different electrolytes in combination with the different major machining parameters were investigated and reported in this article. KOH(aq) electrolyte was found to be the most suitable electrolyte for the fabrication of tungsten microelectrodes. The Taguchi technique was utilized for optimizing the major process control parameters to minimize the taper angle of the fabricated micro-tools. During the tool fabrication process, the deposited electrochemical reaction on the tool surface played an important role to achieve controlled dissolution of the tool materials and helped in producing a uniform surface. The microtools of diameter 40 µm with aspect-ratio of about 175 were fabricated with the optimal settings of dominant machining parameters. The fabricated microtools were used to drill through drill-holes on a nickel plate of thickness 1050 µm using the same µECM setup. The detailed experimental investigations are carried out and conclusive remarks are drawn based on the experimental results.